NS2 is a key determinant of compatibility in reassortant avian influenza virus with heterologous H7N9-derived NS segment - Liu, Yee-Chen; Liao, Guan-Ru; Tsai, April Y.; Tseng, Ching-Yu; Kuan, Chih-Ying; Tsai, Ruei-Sheng; Albrecht, Randy A.; Kuo, Rei-Lin; Cheng, Ivan-Chen; Liang, Wan-Ting; Ou, Shan-Chia; Hsu, Wei-Li (Virus research, 2023)
•Recombinant AIVs bearing various NS segments of H7N9 on the backbone of H6N1 were generated.•The H6N1-based recombinant virus expressing the heterologous NS079 gene was highly attenuated.•Virus expresses H6N1-derived NS2 restored the infection.•Swapping NS2 components changes infection efficiency, suggesting a key role for NS2 as a determinant of viral compatibility upon reassortment. Influenza A viruses are common pathogens with high prevalence worldwide and potential for pandemic spread. While influenza A infections typically elicit robust cellular innate immune responses, the non-structural protein 1 (NS1) antagonizes host anti-viral responses and is critical for efficient virus replication and virulence. The avian influenza virus (AIV) H7N9 initially emerged in China in 2013 and has since crossed the avian-human barrier, causing severe disease in humans. To investigate the influence of the H7N9 NS gene (NS079) on viral replication and innate immune response, we generated several recombinant AIVs bearing various NS079 segments on the backbone of H6N1 (strain 0702). Intriguingly, the recombinant virus bearing the heterologous NS079 gene was highly attenuated compared with virus carrying the homologous NS gene (NS0702). Furthermore, we generated a NS079-0702R virus that expresses a chimeric NS gene in which part of the NS079 effector domain was replaced with the sequence from NS0702. The NS079-0702R virus exhibited significantly enhanced viral yield, approximately 100-fold more than virus bearing NS079. The high infection rate of NS079-0702R virus was reflected by strong induction of IFN and Mx expression in human A549 cells. Intriguingly, our in vitro comparative analysis suggested that the increased NS079-0702R infection capacity was independent of the ability of NS1 to interact with cellular partners, such as PKR and CPSF30. Since partial substitution of the effector domain from NS0702 altered the coding sequence of NS2, we further generated another recombinant virus with NS2 derived from H7N9. Surprisingly, the virus with H7N9-derived NS2 exhibited growth characteristics similar to NS079. Our data demonstrate that swapping NS2 components changes infection efficiency, suggesting a key role for NS2 as a determinant of viral compatibility upon reassortment. These findings warrant further investigation into the precise mechanisms by which NS2 contributes to viral replication and host immunity.1